2022
DOI: 10.3390/vetsci9100555
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Recombinant Rabies Virus Vectors Expressing H or F Protein of Peste des Petits Ruminants Virus

Abstract: Peste des petits ruminants (PPR) is one of the most contagious and fatal diseases of small ruminants in the world and is classified as a category A epidemic disease. It is the target of a global eradication campaign led by the Office International des Epizooties (OIE) and Food and Agriculture Organization of the United Nations (FAO). The PPR live attenuated vaccine is currently the most widely used and approved vaccine, but the use of this vaccine interferes with the serological testing of the PPR elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…They inserted the vesicle membrane glycoprotein H or F genes of PPRV into the backbone plasmid. The viruses constructed in this study have demonstrated good proliferative activity and stability, making them potential candidates for bivalent inactivated vaccines to prevent PPRV and RV in domestic animals ( Figure 6 ) [ 82 ].…”
Section: Advances In Reverse Genetics Of Negative-stranded Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…They inserted the vesicle membrane glycoprotein H or F genes of PPRV into the backbone plasmid. The viruses constructed in this study have demonstrated good proliferative activity and stability, making them potential candidates for bivalent inactivated vaccines to prevent PPRV and RV in domestic animals ( Figure 6 ) [ 82 ].…”
Section: Advances In Reverse Genetics Of Negative-stranded Rna Virusesmentioning
confidence: 99%
“… Advances in reverse genetics of PPRV. PPRV, peste des petits ruminants virus [ 74 , 78 , 80 , 81 , 82 ]. …”
Section: Figurementioning
confidence: 99%